2008
DOI: 10.1029/2008gc002081
|View full text |Cite
|
Sign up to set email alerts
|

Estimating pore‐space gas hydrate saturations from well log acoustic data

Abstract: [1] Relating pore-space gas hydrate saturation to sonic velocity data is important for remotely estimating gas hydrate concentration in sediment. In the present study, sonic velocities of gas hydrate-bearing sands are modeled using a three-phase Biot-type theory in which sand, gas hydrate, and pore fluid form three homogeneous, interwoven frameworks. This theory is developed using well log compressional and shear wave velocity data from the Mallik 5L-38 permafrost gas hydrate research well in Canada and applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 20 publications
1
92
0
Order By: Relevance
“…30% (maximum values of ca. 80%), which is equivalent to or higher than that at other hydrate-bearing sites, such as in permafrost in Canada (Mallik 5L-38), at Mount Elbert in Alaska, in the Gulf of Mexico, within the northern Cascadia margin (Lee & Waite 2008), and in the Nankai Trough offshore from the mouth of the Tenryu River (e.g. Tsuji et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30% (maximum values of ca. 80%), which is equivalent to or higher than that at other hydrate-bearing sites, such as in permafrost in Canada (Mallik 5L-38), at Mount Elbert in Alaska, in the Gulf of Mexico, within the northern Cascadia margin (Lee & Waite 2008), and in the Nankai Trough offshore from the mouth of the Tenryu River (e.g. Tsuji et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between gas hydrate and P-wave velocities can be modeled using a TPE (Leclaire et al 1994;Carcione & Tinivella 2000;Lee 2007) and by assuming that gas hydrate acts as a load-bearing component within sediments. We used a simplified TPE (Lee 2008) to calculate velocities for the gas hydrate-bearing sediments; details of the TPE used for gas hydrate-bearing sediments are given in Lee and Waite (2008) and Lee (2007. The Vp of gas hydrate-bearing sediments (Vp) was calculated as follows:…”
Section: Gas Hydrate Saturationmentioning
confidence: 99%
“…Other procedures are based on seismic data analysis, using velocity seismic models and/or amplitude variations versus offset analysis [23][24][25]. Moreover, some authors have suggested modelling elastic velocities versus gas hydrate concentrations using seismic velocities [26][27][28] or sonic log data [26,29] to obtain information about the hydrate occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Pore-filling hydrate reduces the permeability more significantly than mineralcoating hydrate [57]. Based on the limited data available for gas free, hydrate-bearing systems [58], pore-filling hydrate models provide the best estimates of permeability [59,60].…”
Section: Permeabilitymentioning
confidence: 99%